2013
DOI: 10.1016/j.neuroimage.2013.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Training-mediated leftward asymmetries during music processing: A cross-sectional and longitudinal fMRI analysis

Abstract: Practicing a musical instrument has a profound impact on the structure and function of the human brain. The present fMRI study explored how relative hemispheric asymmetries in task-related activity during music processing (same/different discrimination) are shaped by musical training (quantified as cumulative hours of instrument practice), using both a large (N = 84) cross-sectional data set of children and adults, and a smaller (N = 20) two time-point longitudinal data set of children tracked over 3 to 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 92 publications
3
43
0
6
Order By: Relevance
“…Currently, there is evidence showing that musicianship is associated with specific functional (Ellis et al 2013;Elmer et al 2012;Ohnishi et al 2001) and structural features of the left (and right) PT (Bermudez et al 2009;Elmer et al 2013;Keenan et al 2001;Luders et al 2004;Schlaug et al 1995b), and that these features are associated with better discrimination accuracy for CV syllables and reducedspectrum analogues . However, it still remains concealed whether white matter connectivity between the left and right PT is altered as a function of musical training, to what extent this connectivity pattern contribute to segmental speech processing and PT specialization, and whether the diffusion properties of this specific fibre bundle are related to musical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is evidence showing that musicianship is associated with specific functional (Ellis et al 2013;Elmer et al 2012;Ohnishi et al 2001) and structural features of the left (and right) PT (Bermudez et al 2009;Elmer et al 2013;Keenan et al 2001;Luders et al 2004;Schlaug et al 1995b), and that these features are associated with better discrimination accuracy for CV syllables and reducedspectrum analogues . However, it still remains concealed whether white matter connectivity between the left and right PT is altered as a function of musical training, to what extent this connectivity pattern contribute to segmental speech processing and PT specialization, and whether the diffusion properties of this specific fibre bundle are related to musical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported activation-related changes for visuo-spatial learning (e.g., Hötting, Holzschneider, Stenzel, Wolbers, & Röder, 2013; Küper, Wünnemann, Thürling, et al, 2014; Nemmi, Boccia, Piccardi, Galati, & Guariglia, 2013), motor movements (e.g., Landau & D’Esposito, 2006; Meister, Krings, Foltys, Boroojerdi, Müller, Töpper, & Thron, 2005; Vogt, S., Buccino, G., Wohlschläger et al, 2007), and musical experience (Chen, Rae, & Watkins, 2012; Ellis, Bruijin, Norton, Winner, & Schlaug, 2013; Ellis Norton, Overy, Winner, Alsop, & Schlaug, 2012; Fujioka, Ross, Kakigi, Pantev, & Trainor, 2006; Koelsch, Fritz, Schulze, Alsop, & Schlaug, 2005). Although either learning or just greater experience in visuo-spatial and motor domains is often associated with a reduction in brain activation or skill acquisition (Hötting et al, 2013; Nemmi et al, 2013; Vogt et al, 2007), laterality shifts have been reported for aspects of music learning.…”
Section: Discussionmentioning
confidence: 99%
“…Listening to trained vs. untrained melodies resulted in a reduction of activation in right but not left superior temporal gyrus (Chen et al, 2012). A left hemisphere increase in activation has been associated with hours of musical training for the left superior temporal gyrus (Ellis et al, 2012) and left supramarginal gyrus (Ellis et al, 2013). Similarly, children with violin training showed larger electrophysiologic response over left hemisphere electrode sites to violin tones, compared with their untrained peers (Fujioka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The significantly larger activations of improvising musicians in right hemisphere, in comparison with musically unskilled controls (Harris and de Jong, 2014), might also seem to conflict with the general view that expert musicians process music in the left hemisphere and non-musicians in the right (Fabbro et al, 1990;Evers et al, 1999;Itoh et al, 2001;Bhattacharya and Petsche, 2005;Ellis et al, 2012;Ellis et al, 2013). The results of the present study suggest, however, that right-hemisphere dominance in improvising musicians is associated with their unique ability to perform audiospatial-motor transformations on music they hear, transformations that are associated with a dedicated righthemisphere dorsal network of parietal and premotor areas.…”
Section: Left Hemisphere Dominancementioning
confidence: 99%